Unsieging the siege : the politics of aid convoys to Gaza (2009-2012) - Jemaimah Badaruddin Mustapha (Department of Political Science, International Islamic University Malaysia, 2014)
The aim of this study is to analyse the nature, characteristics and effectiveness of the citizen-led aid convoys to break the siege on the Gaza Strip of Palestine that has been imposed by Israel. This study is significant as the issue became politically important and the convoys attracted global attention. Therefore, it is important to see if there is evidence that convoys do make a difference for the people of Gaza. In particular two large organisations named the Free Gaza Movement and Viva Palestina were extensively examined in this study. Based on data gathered from important people who are the leaders of these organisations as well as the views of the activists who have either joined a convoy or support the cause, this research has found that sending these aid convoys have caused massive awareness around the world, which then created an even bigger movement. Even if the convoys could not force Israel to break the siege, they proved to be useful in shaping international public opinion.